The (in)elasticity of moral ignorance - Marta Serra-Garcia; Nora Szech (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2018)
We investigate the elasticity of preferences for moral ignorance with respect to monetary incentives and social norm information. We propose a model where uncertainty differentially decreases the moral costs of unethical behavior, and benchmark the demand curve for moral ignorance against a morally neutral context. In line with the model, selfishness is a main determinant of moral ignorance, and the demand curve for moral ignorance is highly elastic when information shifts from being costly to incentivized. Moral ignorance is considered morally inappropriate. Providing this information increases moral behavior but does not shift the demand curve for ignorance.
urn:nbn:de:swb:90-892634
Keywords: D83; D91; C91; 330; information avoidance; morality; unethical behavior; social norms